Risk-Taking, Competition and Uncertainty: Do Contingent Convertible (CoCo) Bonds Increase the Risk Appetite of Banks? - Mahmoud Fatouh; Ioana Neamtu; Sweder van Wijnbergen (Tinbergen Institute, 2022)
We assess the impact of contingent convertible (CoCo) bonds and the wealth transfers they imply conditional on conversion on the risk-taking behaviour of the issuing bank. We also test for regulatory arbitrage: do banks try to maintain risk-taking incentives by issuing CoCo bonds, when regulators reduce them through higher capitalization ratios? While we test for, and reject sample selection bias, we show that CoCo bonds issuance has a strong positive effect on risk-taking behaviour, particularly with conversion parameters that reduce dilution of existing shareholders upon conversion. Higher economic volatility amplifies the impact of CoCo bonds on risk-taking.
Keywords: G01; G11; G21; G32; 330; contingent convertible bonds; risk-taking; bank capital structure; selection bias